High rate of virologic suppression with darunavir/ritonavir plus optimized background therapy among highly antiretroviral-experienced HIV-infected patients: results of a prospective cohort study in São Paulo, Brazil - Vidal,José Ernesto (2013)
OBJECTIVES: To assess the virologic and immunological response of darunavir/ritonavir plus optimized background therapy in highly antiretroviral-experienced HIV-infected patients in Brazil. METHODS: Prospective cohort study carried out in a tertiary center in Sao Paulo, Brazil. Three-class antiretroviral-experienced patients with confirmed virologic failure began darunavir/ritonavir plus optimized background therapy (nucleoside/tide reverse transcriptase inhibitors ± raltegravir ± enfuvirtide ± maraviroc) after performing a genotypic resistance assay. Clinical evaluation and laboratory tests were collected at baseline and at weeks 12, 24, and 48. Multivariate analysis was performed to identify predictors of virologic response at 48 weeks. RESULTS: Ninety-two patients were included. The median of darunavir resistant mutation was 1 (range 0-6). The median genotypic sensitivity score in the optimized background therapy was 2 (interquartile range 1-2). At week 48, 83% (95% CI: 75-90%) had an HIV RNA level <50 copies/mL and the median CD4 cell count was 301 (interquartile range 224-445) cells/mm³. Baseline HIV RNA >100 000 copies/mL was inversely associated with virologic success at week 48 (HR: 0.22, 95% CI: 0.06-0.85, p = 0.028). CONCLUSIONS: Darunavir/ritonavir plus optimized background therapy was a highly effective salvage regimen under clinical routine conditions in a referral center in Brazil, which is similar to the reported in high-income countries.